Moral Education of Students In The Culture of The Words Please, Sorry, Thank You and Excuse In Natural Schools - Muttaqin, Muhammad Fauzan; Raharjo, Tri Joko; Suharini, Erni; Wagiran, Wagiran (Universitas Negeri Semarang, 2024)
This research aims to explore students' moral education through cultivating the use of the words